Pengaruh Physicss Education Technology (PhET ) Simulation Terhadap Hasil Belajar IPA Peserta Didik Pada Materi Bentuk dan Perubahan Energi - Taufan Untung Wibowo Silitonga; Haratua Tiur Maria S; Venny Karolina (Departement of Mathematics Education, 2023)
This research is motivated by the ability of students in science lessons on the material of forms and changes in energy which is still low in class V students at SDN 33 North Pontianak. Inappropriate learning media used is the cause of low learning outcomes. This study aims to determine the effect of Physics education technology (PhET ) simulation media on student learning outcomes on the material of energy forms and changes. The study used a quantitative approach with a quasi-experiment method. The sample was selected using random sampling technique, class V A as the experimental class and V B as the kontrol class with a total of 60 students. The study used a Pretest -posttest kontrol group design with an acquisition technique in the form of multiple choice. The analysis used is normality test and paired sample T-test and independent t-test. Based on data analysis, a significant value (2-tailed) of 0.000 <0.05 was obtained, mean ing that H0 was rejected and Hα was accepted, with the results of the mean Posttest learning outcomes in the experimental class of 81.5 while the mean Posttest value in the kontrol class was 39.5. Based on the research, it can be concluded that there is an effect of using PhET on the science learning outcomes of students on the material of forms and changes in energy.